MANAJEMEN KESEHATAN JIWA BERBASIS KOMUNITAS MELALUI PELAYANAN KEPERAWATAN KESEHATAN JIWA KOMUNITAS DI WILAYAH DINAS KESEHATAN KABUPATEN MAGELANG - Sambodo Sriadi Pinilih; Retna Tri Astuti; Muh. Khoirul Amin (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Based on Riskesdas at 2007, Magelang district are in the third rank for prevalence of mental disorders in the population Regency / City in Central Java province. Magelang district was ranked fourth highest for data that deprived people with mental disorders in regencies / cities in Central Java (Bakorwil 2) condition until December 2012 reached 32 cases. Magelang Regency has a variety of potential that can be empowered to support improve mental health services in the community, among others, by having 29 health centers as the spearhead of the provision of health services in the community. There are two public hospitals and one mental hospital, and there are some private hospital and private health clinics. Magelang district health centers in the region have had the nurse in charge of the community mental health program, but the program is not running and there is no allocation of funds related to community mental health programs. Efforts are undertaken to improve mental health nursing services in the community in the form of socialization of mental health and nursing intervention, training for nurses responsible for the mental health program in health centers and training cadres Mental Health (KKJ), as well as the provision of counseling on mental health for the community, especially for families of people with mental disorders. The results obtained from the implementation of the program which has trained 29 health center nurse in charge of mental health programs, has trained 231 people KKJ, detected 85 cases ODGJ health centers in 6 regions designated as target areas. And thereafter the program period 2014-2015 resulted in the level of knowledge KKJ 81% in the high category and 84.5% have a good attitude towards mental health issues. While knowledge is high for understanding the family in caring ODGJ (78.9%).Keywords: Mental health community, Cadre of Mental Health